Creation and Extension of Meaning in Professional Communication - Iļinska, Larisa; Ivanova, Oksana (Research in Language, 2020)
The application of different language resources in professional communication reveals the role of cognition in information processing, the interpretive function of language in knowledge construction, and the interrelation of linguistic and extra-linguistic environments. The aim of the present paper is to examine the development of the language of science and the way it is influenced by history, technology, media, genre, and culture. Integrating cognitive approach and pragmatic analysis, the ways of meaning creation and meaning extension have been studied in the popular science texts. Creative thinking and imagination are considered responsible for innovative, creative and insightful thought in general, and, sometimes, for a much wider range of mental activities.